2014
DOI: 10.3171/2014.1.spine13466
|View full text |Cite
|
Sign up to set email alerts
|

Induction of intervertebral disc cell apoptosis and degeneration by chronic unpredictable stress

Abstract: Object The purpose of this study was to evaluate the effects of chronic unpredictable stress on the intervertebral discs of rats. Methods The cellular events involved in injury- and stress-induced disc degeneration were investigated in male Wistar rats. Disc degeneration and apoptosis were evaluated using microscopic (light and electron) and molecular (immunoblotting and immunohistochemistry) methods. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Previous studies found that apoptosis may be involved in intervertebral disc tissue degeneration of pathophysiological changes, and indicates that apoptosis was important in the process of intervertebral disc degeneration (19). Excessive cell apoptosis results in a reduction in the activity of intervertebral disc cells and a subsequent decrease in extracellular matrix change in synthesis and composition, contributing to the pathology of intervertebral disc degeneration (20). Numerous studies regarding signal transduction pathways have indicated that intervertebral disc cells may be associated with caspase-3 and Bcl-2 signal transduction and apoptosis, regulation of apoptosis may be a method of preventing invertebral disc degeneration (21).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies found that apoptosis may be involved in intervertebral disc tissue degeneration of pathophysiological changes, and indicates that apoptosis was important in the process of intervertebral disc degeneration (19). Excessive cell apoptosis results in a reduction in the activity of intervertebral disc cells and a subsequent decrease in extracellular matrix change in synthesis and composition, contributing to the pathology of intervertebral disc degeneration (20). Numerous studies regarding signal transduction pathways have indicated that intervertebral disc cells may be associated with caspase-3 and Bcl-2 signal transduction and apoptosis, regulation of apoptosis may be a method of preventing invertebral disc degeneration (21).…”
Section: Discussionmentioning
confidence: 98%
“…Disk cell apoptosis, leading to a reduced number of NPCs, has a detrimental role in IDD. 33 In this study, we revealed that the increased apoptosis rate in NPCs by TNFa was significantly reversed with the RADA-KPSS peptide. In addition, the gene expression of pro-apoptotic Bax and antiapoptotic Bcl-2 were analyzed.…”
Section: Discussionmentioning
confidence: 66%
“…Another important finding of this study was that the RADA‐KPSS peptide decreased the incidence of NPC apoptosis. Disk cell apoptosis, leading to a reduced number of NPCs, has a detrimental role in IDD . In this study, we revealed that the increased apoptosis rate in NPCs by TNF‐α was significantly reversed with the RADA‐KPSS peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Disc degenerative disease is a common senile degenerative disease, which seriously affects the quality of life of patients. Apoptosis of nucleus pulposus cells and the decrease of cell viability are the key factors leading to disc degeneration, which is often accompanied by a decrease in extracellular matrix synthesis such as type II collagen and glycoprotein [1,2]. The traditional treatment methods are surgical intervention and conservative treatment, the former is traumatic, the latter is not effective, and the two methods can not fundamentally restore the biological characteristics of the intervertebral disc.…”
Section: Introductionmentioning
confidence: 99%